Evaluation of entamoeba histolytica acetyl co-a synthetase recombinant protein (rehacs) for diagnosis of acute amoebic liver abscess in moribund hamsters - Ching, Guee Cher (2013)
Amoebic liver abscess (ALA) is a potentially fatal infection caused by Entamoeba histolytica. At Hospital Universiti Sains Malaysia, diagnosis of ALA includes detection of antibodies using a commercial kit based on crude soluble antigens (CSA) of E. histolytica. CSA consisted of a cocktail of E. histolytica proteins that are not well-defmed in terms of the characteristics of the proteins and their masses. This study aimed to evaluate the diagnostic potential of a well-defined recombinant protein of E. histolytica acetyl-Co-A synthetase (rEhACS) using serum samples from hamsters with acute fatal ALA. The rEhACS was expressed in E. coli BL21 AI and purified using Ni-NTA resin column under optimized parameters. Purity of the protein was evaluated based on observation of the -77 kDa on SDS-PAGE gel stained with Coomassie brilliant blue. No unspecific band was observed in the gel. The specificity and sensitivity of the purified protein was evaluated via Western blot and enzyme-linked immunosorbent assay (ELISA) using 31 ALA-positive and 5 healthy hamster serum samples. Western blot analysis showed that the sensitivity and specificity ofrEhACS were 58.07% and 100% respectively; while the sensitivity and specificity of the recombinant EhACS used in an ELISA format were both 100%. In conclusion, the -77 kDa recombinant EhACS protein was shown to be important for diagnosis of acute fatal ALA in the animal model and its diagnostic potential in human ALA will be evaluated in future study.